2019
DOI: 10.1515/med-2019-0052
|View full text |Cite
|
Sign up to set email alerts
|

A meta-analysis of robot assisted laparoscopic radical prostatectomy versus laparoscopic radical prostatectomy

Abstract: AbstractObjectiveTo evaluate the efficacy and safety of robot-assisted laparoscopic radical prostatectomy (RALP) and laparoscopic radical prostatectomy (LRP) for the treatment of localized prostate cancer.MethodsMeta-analysis was applied using Review Manager V5.3 softwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 23 publications
1
15
0
3
Order By: Relevance
“…Wang et al . [ 11 ] reported a meta-analysis consisting of mostly observational studies comparing LRP with RARP. The authors found that EBL (95% CI, [-0.84, 0.08]) and positive surgical margin (PSM) rate (odds ratio [OR] 0.97, 95% CI, [0.76, 1.24]) was not significantly different between LRP and RARP.…”
Section: Resultsmentioning
confidence: 99%
“…Wang et al . [ 11 ] reported a meta-analysis consisting of mostly observational studies comparing LRP with RARP. The authors found that EBL (95% CI, [-0.84, 0.08]) and positive surgical margin (PSM) rate (odds ratio [OR] 0.97, 95% CI, [0.76, 1.24]) was not significantly different between LRP and RARP.…”
Section: Resultsmentioning
confidence: 99%
“…In 2013, RALRP was introduced at the Ramathibodi Hospital. In many studies in the past, RALRP has been shown to be more advantageous than LRP [ 17 ] in terms of EBL, operative time, blood transfusion rate, LOS, and adjacent organ injury rate. According to previous studies [ 11 , 18 ], there are ample data from high-volume centres reporting that RALRP has the advantages of fewer postoperative complications compared with LRP.…”
Section: Discussionmentioning
confidence: 99%
“…There are plenty of study data from high-volume centres that have reported on LRP and RALRP as MIS techniques worldwide. A meta-analysis [8] showed that RALRP, with its advantages of few postoperative complications and well-preserved urinary continence and erectile function, was an effective, and safe option for prostate cancer [8,9]. In Thailand, the cost of treatment with RALRP and LRP differs [10], so the total cost is a factor that determines the choice of treatment in shared doctor-patient decisions.…”
Section: Introductionmentioning
confidence: 99%
“…Robotic surgeries in cancer with definitive advantage in terms of ease of surgery and marginal benefits in patient outcome are: & Anterior resection or APR with TME and ANP in carcinoma rectum [4] & Nerve sparing prostatectomy in carcinoma prostate [10] & Partial nephrectomy [11] & Mediastinal tumors [12] & Metastatectomy in the lung, wedge resection, and lobectomy in carcinoma lung [13] & Transoral robotic surgery (TORS) for small pharyngeal wall tumors, tongue base malignancy (avoids mandibulotomy) [14] & Surgery for carcinoma endometrium [15] Though many other procedures are being done robotically, the advantage is not clearly demonstrated with present evidence. However, continued effort and well-conducted studies to look into the long-term outcome may change the opinion in near future.…”
Section: Evidencementioning
confidence: 99%